Positron emission tomographic imaging in drug discovery - Ghosh, Krishna Kanta (2022)
Positron emission tomography (PET) is an extensively used nuclear functional imaging technique, especially for central nervous system (CNS) and oncological disorders. Currently, drug development is a lengthy and costly pursuit. Imaging with PET radiotracers could be an effective way to hasten drug discovery and advancement, because it facilitates the monitoring of key facets, such as receptor occupancy quantification, drug biodistribution, pharmacokinetic (PK) analyses, validation of target engagement, treatment monitoring, and measurement of neurotransmitter concentrations. These parameters demand careful analyses for the robust appraisal of newly formulated drugs during preclinical and clinical trials. In this review, we discuss the usage of PET imaging in radiopharmaceutical development; drug development approaches with PET imaging; and PET developments in oncological and cardiac drug discovery.